2020
DOI: 10.21608/ejabf.2020.80718
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Health Risk, Heavy Metal Pollution Indices and Water Quality of Edku Lagoon- Egypt

Abstract: Contamination of aquatic environment by heavy metals (HMs) is a critical concern due to their potential toxicity and accumulation in aquatic habitats (Jordan et al., 2014; Tscheikner-Gratl et al., 2019). Under certain environmental conditions, HMs could accumulate to a toxic concentration level and then cause significant ecological impacts and problems for human health (Jaishankar et al., 2014; Wongsasuluk et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
3
11
1
1
Order By: Relevance
“…The above results revealed that concentrations of the investigated heavy metals in the two Lakes significantly increase at sites nearest to the drains due to the highly content of these metals in these drains. Similar finding obtained by many researchers (Koussa, 2000;Moussa, 2004;Saeed and Shaker, 2008;Farouk, 2009;Darwish, 2016;El Morshedy, 2017;El-Batrawy et al, 2018;Shetaia et al, 2020).…”
Section: Assessment Of Heavy Metals In Water Of Burullus and Edku Lakessupporting
confidence: 88%
See 1 more Smart Citation
“…The above results revealed that concentrations of the investigated heavy metals in the two Lakes significantly increase at sites nearest to the drains due to the highly content of these metals in these drains. Similar finding obtained by many researchers (Koussa, 2000;Moussa, 2004;Saeed and Shaker, 2008;Farouk, 2009;Darwish, 2016;El Morshedy, 2017;El-Batrawy et al, 2018;Shetaia et al, 2020).…”
Section: Assessment Of Heavy Metals In Water Of Burullus and Edku Lakessupporting
confidence: 88%
“…Barseek Drain transports mainly agricultural drainage water to the lake (Okbah and El-Gohary, 2002; Badr and Hussein 2010). These drains responsible for increasing the contamination in the Lake and Increasing contamination associated with increasing levels of heavy metals which adversely affected the fishery (Shetaia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As per Wilcox and USSL diagram, all the stations denote ‘excellent to good’ category for irrigation suitability of water with ‘high to medium’ permeable soil category in three phases. An important ecological factor salinity has a significant role inthe survival of organisms ( Shetaia et al, 2020 ). However, Potential Salinity is more dynamic in nature near coastal areas than inland water ( Shil et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many fish species are collected from Edku Lake. These fish species included tilapia species (Farouk et al 2020;Shetaia et al, 2020). Tilapia species such as Oreochromis niloticus, Tilapia zillii, Sarotherodon galilaeus, and Oreochromis aureus, were ranked first followed by Clarias gariepinus in the total fish production of the Egyptian Lakes (Zahran et al 2015;Helal et al 2020).…”
Section: Introductionmentioning
confidence: 99%